CULTURAL DEVELOPMENTS IN ELECTRONIC LAW ENFORCEMENT IN CRIMINAL ACTS OF THEORY IN INDONESIA - Yusep Mulyana (SAMPURASUN, 2021)
The culture of proving electronic evidence in law enforcement of criminal acts of terrorism in Indonesia is Law Number 11 of 2008 concerning Information and Electronic Transactions ("UU ITE") which provides a legal basis for the legal culture of electronic and formal evidence and material. requirements for electronic evidence to be accepted in court. Electronic Evidence is Electronic Information and/or Electronic Documents that meet the formal requirements and material requirements stipulated in the ITE Law. Article 5 paragraph (1) of the ITE Law stipulates that Electronic Information and/or Electronic Documents and/or their printouts are legal evidence. The implementation of the regulation of electronic evidence in law enforcement of criminal acts of terrorism in Indonesia is the use of evidence in the form of wiretapping and video recordings which were actually applied in the 2002 Bali Bombing Case. 1 of 2002 concerning the Eradication of Criminal Acts of Terrorism. Despite the controversy, the Public Prosecutor emphasized that the reading of the statements of witnesses from Malaysia and Singapore who were unable to attend the trial was legal because it was in accordance with the description of the evidence in the law. The same is regulated in the Law on Information and Electronic Transactions. Article 5 states that electronic information and/or printed electronic information are legal evidence and have legal consequences. Of course, electronic information is declared valid if it uses an electronic system in accordance with the applicable laws and regulations.